HER2 Exon 20 Insertion Mutations in Lung Adenocarcinoma: Case Series and Response to Pyrotinib - Zhang, Xinyong; Lv, Jialin; Wu, Yuhua; Qin, Na; Ma, Li; Li, Xi; Nong, Jingying; Zhang, Hui; Zhang, Quan; Yang, Xinjie; Shi, Huibo; Wang, Jinghui; et al. (Frontiers in Oncology, 2020)
HER2 mutations have emerged as oncogenic driver gene mutations in non-small cell lung cancer (NSCLC), which have not been descried detailed like other driver gene mutations. Here, 295 patients with advanced lung adenocarcinoma were retrospectively screened for HER2 mutations using next-generation sequencing (NGS), and the positive cases were validated by Sanger sequencing. We identified 5 cases with HER2 exon 20 insertions, representing 1.7% of 295 lung adenocarcinomas. Among them, 4 different subtypes of HER2 exon 20 insertions were identified, including a rare subtype G778_S779insCPG never reported before, with a partial response (PR) to pyrotinib and progression-free survival (PFS) of 12.8 months. Our findings reveal that HER2 exon 20 insertion mutations were detected in a small subset of lung adenocarcinomas. Given the different drug sensitivity, determining the mutation subtype by next-generation sequencing at the time of diagnosis might make sense.